Bilateral Cooperation Between The Government of Indonesia Malaysia On Management Border Territory - Jawahir Thontowi (Unisia, 2011)
This study reveals that bilateral cooperation between the government of Indonesia-Malaysia began continue since 1960. It was until 1974, two Governments signed MoU and followed to by 25 join diplomacy meetings in persuing border problem. In practice however, it is found it difficult for Indonesian government to progress people development in border area. Not only because the Indonesian and Malaysian negotiation diplomacy are less effective to prevent and control border area, but rather because too many factors are faced by central and local governments of Indonesian, to issue aspecial regulation which is internally relevant to solve the problem of border area.Keywords: International Law, Border Area, Cooperation, Total Diplomacy and-Local Diplomacy, tangible and untangible factors.